The Preferences of Nirwana Village Families in Choosing Islamic Boarding Schools as Educational Institutions for Their Children - Amma, Tasurun; Maghfiroh, Ani; Purnomo (Kirana Publisher (KNPub), 2025)
This research aims to explore the preferences of families in Nirwana Village in choosing Islamic boarding schools (Pondok Pesantren) as educational institutions for their children. Employing a qualitative descriptive method, the study gathers data through interviews, observation, and documentation involving selected families and pesantren administrators. The findings reveal that religious values, discipline, character education, accessibility, cost, and the reputation of pesantren are the main factors influencing family choices. Families view pesantren not only as centers of religious knowledge but also as institutions that shape the moral and spiritual character of children. The study concludes that cultural and religious traditions in Nirwana Village play a significant role in sustaining the preference for pesantren education, and understanding these preferences can support educational policy planning and pesantren development.